2016
DOI: 10.1007/s10140-016-1417-y
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of plain radiography for pediatric cervical spine injury

Abstract: Society of EmergencyAbstract Pediatric patients with suspected cervical spine injuries (CSI) often receive a computed tomography (CT) scan as an initial diagnostic imaging test. While sensitive, CT of the cervical spine carries significant radiation and risk of lethal malignant transformation later in life. Plain radiographs carry significantly less radiation and could serve as the preferred screening tool, provided they have a high functional sensitivity in detecting pediatric patients with CSI. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Despite a movement toward CT as the initial screening tool, cervical spine X-ray followed by MRI remains a viable alternative to reduce radiation. Several recent reports have demonstrated excellent sensitivity of X-ray for CSI [20, 21]. Lindholm et al [22] showed that even a single lateral-view X-ray was equivalent to multiple views and had 100% sensitivity for bony injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a movement toward CT as the initial screening tool, cervical spine X-ray followed by MRI remains a viable alternative to reduce radiation. Several recent reports have demonstrated excellent sensitivity of X-ray for CSI [20, 21]. Lindholm et al [22] showed that even a single lateral-view X-ray was equivalent to multiple views and had 100% sensitivity for bony injuries.…”
Section: Discussionmentioning
confidence: 99%
“…If CSI is suspected, various international trauma guidelines recommend plain radiography of the C-spine as primary imaging in children [11,16]. Its sensitivity for detecting CSI is higher than 90% [9,11,[17][18][19]. A CT scan of the C-spine is only indicated in those patients for whom a fracture is seen on plain radiography or for whom there is clinical suspicion of CSI despite a negative result with plain radiography [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional film images are frequently the initial imaging modality of choice (14). Cervical spine radiographs have been shown to have high sensitivity, and cervical spine trauma algorithms with radiography used as the initial examination have demonstrated high sensitivity and specificity for cervical spine injuries (17,18). The recommended radiographic series for pediatric cervical spine trauma consists of frontal and lateral radiographs (14).…”
Section: Cervical Spine Radiographymentioning
confidence: 99%